Contributing Cost Variation Factors in Highway Projects - Samiullah Sohu; Abd Halid Abdullah; Sasitharan Nagapan; Ashfaque Ahmed Jhatial; Muhammed Tahir (Salehan Institute of Higher Education, 2018)
Cost overrun is known as when the final cost of any project surpasses the sectioned cost of the project at the floating of tender. Cost overrun or cost variation overrun is the main problem in the construction of highway projects in Sindh Province of Pakistan. To attain the main objective of the research a literature review was conducted and 64 general factors of cost overrun were found in construction industry. A questionnaire was developed and distributed among 28 well experienced experts having maximum experience in construction of building projects. Gathered data was analyzed by method of average index. Results shows that main and causative factors of cost variation were financial and cash issues faced by owner, slow information between parties, change in price of material, delay of design, poor site management, payment and financial issues problem faced by the contractor and delay in decision making. This research can help petitioners of highway projects to overcome these main and causative factors of cost.